An uncommon case of chronic myeloid leukemia with variant cytogenetic - Abdullah, Mohamed A; Amer, Aliaa; Nawaz, Zafar; Abdullah, Ali S; Al-Sabbagh, Ahmad; Kohla, Samah; Nashwan, Abdulqadir J; Yassin, Mohamed A (Acta Biomedica Atenei Parmensis, 2018)
Chronic Myeloid Leukemia (CML) is myeloproliferative neoplasm characterized by Philadelphia chromosome which is a balanced translocation between chromosome 9 and 22 in 90% of cases. However, variant cytogenetic still happens in 5-10 % of cases, the importance of which is controversial as well as its response to therapy, prognosis and progression to acute leukemias. Here we report a male patient with CML and variant cytogenetic who responded to low dose of Dasatinib (50 mg daily).